3D Geomechanical Modeling and Prediction of Fractures in the Bozi Ultra-Deep Gas Field in the Kuqa Depression of Tarim Basin - Xu, Ke; Zhang, Hui; Wang, Haiying; Wang, Zhimin; Yin, Guoqing; Wang, Xiaoxue; Kang, Tingting; Huang, Li; Wang, Zhaohui; Zhao, Wei (Frontiers in Earth Science, 2022)
In order to clarify the fracture distribution characteristics of the Bozi gas field in the Kuqa Depression, based on the statistics of fracture parameters from core data and imaging logging, the three-dimensional (3D) structural model of the complex thrust structure is established by using the voxel-based morphometry (VBM) structural framework modeling technology; the 3D heterogeneous rock mechanics field in the study area is constructed by well-to-seismic integration. The relationship between in situ stress field and fracture parameters is established under the consideration of rock fracture criterion, and fracture prediction of the Cretaceous reservoir in the Bozi gas field is carried out with the finite element numerical simulation method. Considering the influence of in situ stress field on fracture parameters, fracture activity is analyzed. The results show that the Cretaceous reservoirs in the Bozi gas field generally develop fractures, most of which are high-angle shear fractures of tectonic origin and are semi-filled or unfilled. The fracture distribution of the Bozi gas field is obviously controlled by local structures such as folds and faults. From north to south, the fracture development gradually weakens, and the fracture density of Bozi 104 and Bozi 102 fault blocks in the north is the highest. The fracture in the northern fault block of the Bozi gas field shows high activity, while that in the southern fault block shows low activity. The fractures in the higher structural parts of most fault blocks show high activity.